Improving Credibility by Delegating Judicial Competence: The Case of the Judicial Committee of the Privy Council - Stefan Voigt; Michael Ebeling; Lorenz Blume (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2004)
It is argued that government credibility is an important resource and that it can be improved by delegating decision-making competence beyond the nation-state. It is hypothesized that such delegation should result in higher income and growth. Some former British colonies retained the Judicial Committee of the Privy Council as their final court of appeals even after independence. This court is thus taken as a natural experiment to test our hypothesis. It turns out that retaining the jurisdiction is indeed significant for explaining economic growth.
Keywords: P51; K11; H11; O57; N40; K41; 330; Credibility; Delegation of Competence; Judicial Independence; Economic History; Judicial Committee of the Privy Council; Justiz; international; Wirtschaftswachstum; Wirtschaftsgeschichte; Commonwealth; England